APPLICATION OF PSAK NO. 109 (REVISED 2022) ON REPORTING FINANCIAL ACCOUNTING OF ZAKAT AND INFAQ/SEDEKAH AT THE NATIONAL AMIL ZAKAT AGENCY (BAZNAS) PROBOLINGGO CITY - Judi Suharsono; Dyah Ayu Perwitasari; Putri Devita Sari; M. Novan Fithrianto; Mufid Andrianata (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to analyze the comparison of the application of PSAK No. 109 of 2010 and PSAK No. 109 Revised 2022 and the impact of the application of PSAK No. 109 Revised 2022 on the transparency and accountability of financial statements. Methods: The research method used is descriptive qualitative with interview and documentation techniques. This research was conducted at the National Amil Zakat Agency (BAZNAS) of Probolinggo City. Results: The results of this study indicate that the National Amil Zakat Agency (BAZNAS) of Probolinggo City has managed zakat, infaq, and sadaqah according to sharia principles and PSAK No. 109, with financial statements that reflect effective and transparent fund management. However, the implementation of PSAK Revision 2022 is not yet fully complete, especially in the disclosure of non-cash assets and related party relationships, which are important to improve transparency. The implementation of this PSAK improves transparency, asset recognition, accountability, and reconciliation of financial statements. The main suggestion is that BAZNAS Probolinggo City immediately fully implements PSAK No. 109 Revision 2022 and conducts staff training so that the management of zakat, infaq and sadaqah funds is more professional and reliable. Keywords: Islamic accounting, PSAK and ZIS